Floating Multi-Focus Metalens for High-Efficiency Airborne Laser Wireless Charging - Zheting Meng; Yuting Xiao; Lianwei Chen; Si Wang; Yao Fang; Jiangning Zhou; Yang Li; Dapeng Zhang; Mingbo Pu; Xiangang Luo (Photonics)
Laser wireless power transfer (LWPT) offers a transformative approach to wireless energy transmission, addressing critical limitations in unmanned aerial vehicles (UAVs) such as battery energy limitation. However, challenges like beam divergence, non-uniform irradiation, and alignment instability limit its practical application. Here, we present a lightweight air-floating metalens platform to overcome these barriers. This innovative lens focuses laser beams near the photovoltaic receiver with an energy distribution uniformity across a single spot at the focal plane that is 50 times greater than that of a conventional Gaussian beam spot, achieving a multi-spot energy distribution uniformity of up to 99% theoretically. Experimentally, we achieved 75% uniformity using a metalens sample. Simultaneously, our system maintains superior beam quality within a dynamic range of 4 m and enhances charging efficiency by 1.5 times. Our research provides a robust technical solution to improve UAV endurance, enabling efficient, long-range wireless power transfer and opening broader technological implications.